The increased main branch to stent diameter ratio is associated with side branch decreased coronary flow in "true" coronary artery bifurcations treated by "provisional" stenting - a two-dimensional quantitative coronary angiography study - Ilić Ivan; Vidaković Radosav; Janićijević Aleksandra; Stefanović Milica; Kafedžić Srđan; Cerović Milivoje; Milićević Dušan; Obradović Gojko; Jovanović Vladimir; Stanković Ivan; Putniković Biljana; Nešković Aleksandar N. (Vojnosanitetski Pregled)
Background/Aim. Percutaneous coronary interventions (PCI) in bifurcation lesions having more than 50% stenosis of both the main branch (MB) and the side branch (SB) remain challenging. Measurements of the vessel diameters and angles using quantitative coronary angiography (QCA) software have been used in evaluating PCI outcomes. We investigated potential effects of provisional stenting of the MB on SB coronary blood flow by determining quantitative vessel parameters in “true” non-left main coronary bifurcation lesions using conventional two-dimensional QCA. Methods. The study was prospective and conducted in a highvolume university PCI center. Study included patients with “true” native coronary artery bifurcations (Medina 1.0.1; 0.1.1; 1.1.1) treated with “provisional” stenting of the MB. Patients were excluded from the study if having left ventricular ejection fraction of less than 30%, having renal failure with creatinine clearance below 30 mL/kg/m2 or bifurcation lesions within the culprit artery causing myocardial infarction, grafted surgically or previously treated by PCI. QCA analysis included measurements of reference vessel diameters (RVD), diameter stenosis (DS) and bifurcation angles. Results. The study included 70 patients with 72 “true” non-left main bifurcations. Most of the bifurcations were located in the left anterior descending (LAD) – diagonal (Dg) territory. Compromise of the SB ostium defined as thrombolysis in myocardial infarction (TIMI) < 3 coronary flow occurred in 17/72 (23.6%) bifurcations. It was treated by either balloon angioplasty only of the SB ostium (9/17, 52.9%) or stent implantation [8/17 (47.1%)]. In a logistic regression analysis, including previously recognized predictors of SB compromise (bifurcation’s angles, RVD, DS and ratio of MB RVD to stent diameter ratio), only MB RVD to stent diameter ratio after PCI remained independent predictor of SB coronary flow compromise after stent implantation in the MB [OR 2.758 (95% CI 1.298–5.862); p = 0.008]. Conclusions. It appears that SB decreased coronary blood flow after “provisional” stenting in “true” non-left main bifurcations is associated with greater MB to stent diameter ratio.